2022
DOI: 10.3389/fmed.2022.950564
|View full text |Cite
|
Sign up to set email alerts
|

Moderate sedation by total intravenous remimazolam-alfentanil vs. propofol-alfentanil for third molar extraction: A prospective randomized controlled trial

Abstract: BackgroundOral dental treatment cause anxiety, fear, and physical stress. This study aimed to investigate the efficacy and safety of moderate sedation by remimazolam with alfentanil vs. propofol with alfentanil in third molar extraction.MethodsThis single-center, randomized, single-blind clinical trial included 100 adults who underwent third molar ambulatory extraction. All patients had continuous infusion of Alfentanil 0.2 μg/kg/min. Group remimazolam with alfentanil (group RA) had an induction dose of 80 μg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
1
10
1
Order By: Relevance
“… 17 18 Remimazolam combined with opioid analgesics can be used for ambulatory sedation. 19 Phase III clinical studies of this agent have used remimazolam in colonoscopy, 20 fibrobronchoscopy 21 and for the induction and maintenance of general anaesthesia. 22 23 These studies show that when compared with other similar products, remimazolam exhibited a quick action onset, rapid metabolism and no accumulation.…”
Section: Introductionmentioning
confidence: 99%
“… 17 18 Remimazolam combined with opioid analgesics can be used for ambulatory sedation. 19 Phase III clinical studies of this agent have used remimazolam in colonoscopy, 20 fibrobronchoscopy 21 and for the induction and maintenance of general anaesthesia. 22 23 These studies show that when compared with other similar products, remimazolam exhibited a quick action onset, rapid metabolism and no accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies confirmed that RT could be safely and effectively used for sedation in outpatient surgeries, such as gastrointestinal endoscopy (Rex et al, 2018;Lu et al, 2022;Xin et al, 2022), bronchoscopy (Pastis et al, 2019), tooth extraction (Zhao et al, 2022), hysteroscopy (Zhang et al, 2021), or induction and maintenance of general anesthesia (Zhou et al, 2020;Mao et al, 2022). RT could also provide enough sedative effect and safety for special patients, such as elderly patients (Liu et al, 2022;Tan et al, 2022) and patients with liver cirrhosis (Cao et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…Some studies ( Antonik et al, 2012 ; Zhou et al, 2015 ) proved the varied advantages of RT, such as rapid-onset, controllable inhibition of cardiovascular and respiratory systems, inactive metabolites through plasma esterase metabolism, low potential of drug interaction, and reversibility. Therefore, it can be used for sedation outside the operating room, such as bronchoscopy ( Pastis et al, 2019 ), hysteroscopy ( Zhang et al, 2021 ), molar extraction ( Zhao et al, 2022 ), and other endoscopic examinations ( Rex et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are currently few research reports that have evaluated the efficacy and safety of remimazolam for sedation during dental procedures. A single-center, randomized, single-blind clinical trial with alfentanil in adults undergoing outpatient third molar extractions reported a lower incidence of adverse events, significantly lower incidence of injection pain, and significantly shorter recovery and discharge times in the remimazolam group compared to the propofol group [ 35 ]. Another prospective, randomized, controlled, single-center trial of 40 patients undergoing outpatient oral surgery in China found that the remimazolam group had a significantly higher sedation success rate and faster recovery compared to the midazolam group [ 36 ].…”
Section: Discussionmentioning
confidence: 99%